Survey of the Aphid Parasitoids (Hymenoptera: Braconidae: Aphidiinae) of Costa Rica with Information on Their Aphid (Hemiptera: Aphidoidea): Plant Associations - Daniel Zamora Mejías; Paul E. Hanson; Petr Starý (Psyche: A Journal of Entomology)
Species of Aphidiinae (Braconidae) have never been surveyed in Central America. Here we present the results of an initial inventory of the aphidiine species of Costa Rica and record the presence of ten species (four undetermined), in six genera. The material was obtained by rearing aphids from both crop and noncrop plants throughout the country. In total 2832 aphidiine specimens were reared from 24 species of aphids. Aphidius colemani and Lysiphlebus testaceipes, which are probably not native to Costa Rica, accounted for nearly 90% of all the specimens. Many of the other aphidiines are also probably exotic species, as are most of their host aphids.